Determining the Optimal Capital Structure of PT. Waskita Karya Tbk (Persero) - Bintang Raihandika, Arya; Yudha Sudrajad, Oktofa Yudha Sudrajad (Journal of Accounting and Finance Management, 2025)
PT Waskita Karya Tbk, as one of the leading State-Owned Enterprises in Indonesia, plays an important role in national infrastructure development. However, major challenges arise due to the company's dependence on debt financing which causes an unbalanced capital structure. This study aims to determine the optimal capital structure of PT Waskita Karya and provide strategic solutions to support its business sustainability. Based on the analysis of financial projections for 2025, the optimal capital structure can be achieved at a debt ratio of 15%, with a Weighted Average Cost of Capital (WACC) of 7.50%. In this condition, the company's value can be maximized to IDR25,175 billion. This study recommends three main steps: debt restructuring through negotiation and debt-to-equity swap, sale of non-strategic assets to pay off high-interest debt, and operational efficiency with a focus on high-value projects. This study emphasizes the importance of strategic capital structure management for the sustainability of PT Waskita Karya. With targeted implementation, the company is expected to reduce financial risk, increase company value, and remain a reliable partner in national infrastructure development.